2003
DOI: 10.1354/vp.40-6-659
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma Multiforme: Clinical Findings, Magnetic Resonance Imaging, and Pathology in Five Dogs

Abstract: Abstract. Although glioblastoma multiforme (GBM), a World Health Organization grade IV astrocytoma, is the most common primary brain tumor in humans, in dogs GBM is relatively rare, accounting for only about 5% of all astrocytomas. This study presents combined clinical, neuroimaging, and neuropathologic findings in five dogs with GBM. The five dogs, aged from 5 to 12 years, were presented with progressive neurologic deficits that subsequent clinical neurologic examination and neuroimaging studies by magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
128
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(138 citation statements)
references
References 25 publications
3
128
1
2
Order By: Relevance
“…Veterinary trials with toceranib and masitinib have shown benefit in several cancers but have not been reported for brain tumors. Documented overexpression of VEGF, VEGF receptors, and PDGFR alpha in some canine brain tumors108, 109, 110, 111, 112, 113, 114, 115, 116 may justify trials with these or similar small molecules in defined patients.…”
Section: Novel Therapiesmentioning
confidence: 99%
“…Veterinary trials with toceranib and masitinib have shown benefit in several cancers but have not been reported for brain tumors. Documented overexpression of VEGF, VEGF receptors, and PDGFR alpha in some canine brain tumors108, 109, 110, 111, 112, 113, 114, 115, 116 may justify trials with these or similar small molecules in defined patients.…”
Section: Novel Therapiesmentioning
confidence: 99%
“…In addition, there is a high correlation of neuroimaging features observed with magnetic resonance imaging scans in canine and human GBM, which is used as a diagnostic tool for canine GBM. Peritumoral edema is a consistent finding in both human and canine GBM (30,35).…”
mentioning
confidence: 82%
“…Canine GBMs are histopathologically indistinguishable from human GBMs (30). Both are highly infiltrative, contain areas of intratumoral necrosis, pseudopalisading, hemorrhage, cellular pleomorphism, nuclear atypia, abnormal mitosis, and endothelial proliferation (34).…”
mentioning
confidence: 99%
“…Previously, canine gliomas have been shown to contain common alterations observed in human gliomas, including EGFR expression and amplification, VEGF expression and aberrant p53 overexpression and gene mutation. [12][13][14] Of note, IDH1 and IDH2 are highly conserved between dog and human, with 96.9 and 96.4% identity at the protein level, respectively (HomoloGene). The arginines mutated in human gliomas are also conserved between these species, with canine IDH1 R132 corresponding to human IDH1 R132 and canine IDH2 R238 corresponding to human IDH2 R172.…”
Section: Dear Editormentioning
confidence: 99%